MAX STIRNER's EGOISM - Jenkins, John (Heythrop journal, 2009)
My aim in what follows is to provide and criticise a consistent account of Stirnerian egoism. Despite the many obscurities and complexities surrounding Stirner's conception of self-interested action, a detailed examination of The Ego and Its Own does, I believe, offer us an interpretation that remains true to the overall aims of the book. My main concern throughout will be to focus on the interpretation of Stirner as a psychological egoist. I believe that the textual evidence in favour of viewing Stirner's brand of egoism in these terms is overwhelming. The result of this exegesis is at the same time a reply to David Leopold's claim that, in The Ego and Its Own, the evidence for Stirner's commitment to this version of egoism is scarce and unconvincing. If my understanding of Stirner's book is correct, his advocacy of psychological egoism is an unwelcome consequence for the Stirnerian viewpoint, given the weaknesses of psychological egoism as a theory of human motivation. It is also damaging for Stirner's conception of selfhood.